Functionalizable Silica-Based Micron-Sized Iron Oxide Particles for Cellular Magnetic Resonance Imaging. Issue 11 (November 2013) - Raschzok, Nathanael; Langer, Carolin M.; Schmidt, Christian; Lerche, Karl H.; Billecke, Nils; Nehls, Kerstin; Schlüter, Natalie B.; Leder, Annekatrin; Rohn, Susanne; Mogl, Martina T.; Lüdemann, Lutz; Stelter, Lars; et al.
Cellular therapies require methods for noninvasive visualization of transplanted cells. Micron-sized iron oxide particles (MPIOs) generate a strong contrast in magnetic resonance imaging (MRI) and are therefore ideally suited as an intracellular contrast agent to image cells under clinical conditions. However, MPIOs were previously not applicable for clinical use. Here, we present the development and evaluation of silica-based micron-sized iron oxide particles (sMPIOs) with a functionalizable particle surface. Particles with magnetite content of >40% were composed using the sol-gel process. The particle surfaces were covered with COOH groups. Fluorescein, poly-l-lysine (PLL), and streptavidin (SA) were covalently attached. Monodisperse sMPIOs had an average size of 1.18 μm and an iron content of about 1.0 pg Fe/particle. Particle uptake, toxicity, and imaging studies were performed using HuH7 cells and human and rat hepatocytes. sMPIOs enabled rapid cellular labeling within 4 h of incubation; PLL-modified particles had the highest uptake. In T2*-weighted 3.0 T MRI, the detection threshold in agarose was 1, 000 labeled cells, whereas in T1-weighted LAVA sequences, at least 10, 000 cells were necessary to induce sufficient contrast. Labeling was stable and had no adverse effects on labeled cells. Silica is a biocompatible material that has been approved for clinical use. sMPIOs could therefore be suitable for future clinical applications in cellular MRI, especially in settings that require strong cellular contrast. Moreover, the particle surface provides the opportunity to create multifunctional particles for targeted delivery and diagnostics.